Concentración de metales pesados en sedimentos del Refugio de Vida Silvestre Isla Corazón y Fragatas, cantón Sucre- Manabí - Álava Vera, Jefferson Leonardo (2022)
The present investigation evaluated the concentrations of lead (Pb), cadmium (Cd) and mercury (Hg) in sediments in the Isla Corazón y Fragatas Wildlife Refuge during the months of May, July and August 2021. According to the recognition of the area of study, five sampling points were produced in strategic areas and with the collection of information from the observation sheet and the interview, the productive activities around the Refuge were identified. The concentrations of lead, cadmium and mercury in sediments were determined, which reported Pb values of (35.878 to 63.520 mg/kg); Cd from (0.461 to 1.531 mg/kg) and Hg from not detected (N/D). The data was compared with the international environmental regulations Canadian Council of Ministers of the Environment, showing that the concentrations of Pb and Cd exceed the maximum permissible limit, except for the month of May, when the levels of Cd are within the established range. On the other hand, the concentrations of Hg were not detected, which means that there is no presence of this metal in the sediment. Pearson correlations were determined, showing that there are no statistical connections between the physical parameters of the water and the sediments with the concentrations of Pb and Cd, except for the salinity in the sediments versus the concentration of Pb, which has statistical significance.